2023
DOI: 10.1002/ddr.22028
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin‐1 mimic peptide PKHB1 induced endoplasmic reticulum stress‐mediated but CD47‐independent apoptosis in non‐small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is one of the most common malignancies with high morbidity and mortality. PKHB1, a serum-stable Thrombospondin-1 (TSP-1) mimic peptide, has shown some effective ability in triggering cell death against several cancers. Here, we aimed to study the potential biological function of PKHB1 and its molecular mechanism in NSCLC. Our results revealed that PKHB1 significantly suppressed NSCLC cell proliferation, cell migration, and induced apoptosis in a dose-dependent manner. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…CD47 is a leading key immune checkpoint in cancer treatments [33,34]. The western blot assay showed that chaetocin suppresses the CD47 expression at the mRNA level.…”
Section: Chaetocin-mediated Cd47 Expression Decreases In A549 Cellsmentioning
confidence: 99%
“…CD47 is a leading key immune checkpoint in cancer treatments [33,34]. The western blot assay showed that chaetocin suppresses the CD47 expression at the mRNA level.…”
Section: Chaetocin-mediated Cd47 Expression Decreases In A549 Cellsmentioning
confidence: 99%